Microbiological guidelines of medium najs (filth) contamination in Halal ready to eat food - Abu Bakar, Ibrahim; Abdul Rafa, Ainin Azwani; Abdullah Sani, Norrakiah (2015)
This study was conducted to evaluate the severity of najs (filth) contamination in ready to eat food as to confirm the definition of halal food which suppose not contaminated with najs mutawwassitah (medium filth). A total of 52 human stools samples were collected and the screening of bacteria in the human stools samples were done according to traditional microbiological analysis methods. Determinations of bacterial growth curves were performed using NanoDrop 1000 UV-VIS Spectrophotometer at 630nm where the initial and end of log times for each of bacteria was determined. The growth evaluation of fecal borne bacteria in ready to eat food was done using prepared fried rice samples which were prepared at food preparation laboratory. The results showed that healthy human stools which fall under najs mutawassitah contain high amount of presumptive pathogenic bacteria specifically E. coli, S. aureus, B. cereus, Aromonas spp. and Salmonella spp. at different mean values. Average lag phase time for faecal borne bacteria is about 60 minutes (one hour). Thus consuming food before one hour should not give any significant health effect. Consuming food which contains faecal borne bacteria within one to two hours will give either no risk or low risk health effect. Consuming food after two hours has medium risk. Consuming food after three or four hours has high health risk. If the level of health risk is translated according to syariah law, RTE food which contaminated with more than 2 drops of human stools or contaminated with small amount (1-2 drops) of human stools and left over at ambient temperature more than 4 hours is considered as syubhah/makhrooh (doubtful) to be eaten.